Acute Fibrinous and Organizing Pneumonia and Undifferentiated Connective Tissue Disease: A Case Report - Valéria Valim; Roberta Hora Rocha; Roberta Barcelos Couto; Thaysa Simões Paixão; Érica Vieira Serrano (Case Reports in Rheumatology)
Acute fibrinous and organizing pneumonia (AFOP), recently described, is a histologic pattern characterized by the presence of fibrin “balls” within alveolar spaces. The term undifferentiated connective tissue disease (UCTD) is used to identify autoimmune systemic diseases that do not fulfill the criteria to be classified as a definitive connective tissue disease. The AFOP has never been reported in association with UCTD. The present reported case is a 39-year-old Caucasian, female with dry cough and progressive dyspnea. Eight months later, she was diagnosed with “organizing pneumonia” based on clinical history and radiologic images. She manifested Raynaud’s Phenomenon, sicca syndrome, boot and gloves neuropathic pain, and previous hypothyroidism. Antinuclear antibody, rheumatoid factor, and specific autoantibodies were negative. Salivary gland biopsy and electroneuromyiography were normal. The capillaroscopy showed a “scleroderma” pattern with capillary deletion and ectasia. She experienced clinical and radiologic worsening. Despite being submitted to cyclophosphamide pulse, she developed hemorrhage and then died. Thoracotomy pulmonary specimen showed histological pattern of AFOP. This paper shows a rare association of AFOP with UCTD.